Development of a Mobile App for Smoking Cessation: a Qualitative Study - Hargono, Arief; Ni, Zhao; Artanti, Kurnia Dwi; Nastiti, Rizma Dwi; Martini, Santi (Unnes Journal of Public Health, 2024)
Smoking is a public health concern in Indonesia. A challenge facing Indonesian healthcare system is that the use rate of in-person smoking cessation counseling is low due to smokers’ concerns about their privacy. This challenge has limited the ability of Indonesian health researchers and policy makers to develop and implement evidence-based practices to prevent smoking. The development of digital technologies in Indonesia has offered various opportunities to address this issue. Mobile devices are ubiquitous in Indonesia and have the potential to deliver counseling services for smokers. This study was part of the Mobile Application System for Smoking Cessation program and aimed to investigate the culturally-tailored features of mobile apps to prevent smoking in Indonesia. Data were collected through structured interviews and Focus Group Discussions (FGDs) among Indonesian policy makers and experts from universities and NGOs. We also reviewed relevant documents recommended by participants. We found that to develop a culturally-tailored mobile app for smoking cessation in Indonesia, it is important to understand smokers’ characteristics, smoking status, smoking behavior, and level of motivation to quitting smoking. We also found that following the World Health Organization’s 5A (Ask, Assess, Advise, Assist, Arrange) and 5R (Relevance, Risk, Reward, Roadblocks, Repetition) strategies is a key to improve the feasibility and acceptability of a smoking-cessation mobile app. App-based interventions need to be integrated with the practices performed by counselors and health workers and should be easily accessed by smokers.